MANAJEMEN PEGAWAI APARATUR SIPIL NEGARA MENUJU GOOD GOVERNANCE - Bhudianto, Wahyu (Transformasi, 2015)
Civilian employees of the state apparatus is one of the pillars in achieving Good Governance . Good governance is not just a concept that needs to be socialized , but need to be applied at all levels of government everywhere. State Civil apparatus resource is expected to provide services and performance betanggung responsible in order to reflect good governance , employees of the State Civil Apparatus not just wait for what later steps taken by the government to improve its performance , but these employees will be able to take the opportunity of its own to create a breakthrough that could improve their quality or performance in realizing good governance .Keydord: Governance, apparatus, civil.